2001
DOI: 10.1177/070674370104600908
|View full text |Cite
|
Sign up to set email alerts
|

Validation de la version française du Health of the Nation Outcome Scales (HoNOS-F)

Abstract: Results of the present study converge with those obtained on the original widely used English version. Therefore, we suggest that clinicians use the questionnaire by referring to each item separately and by considering such patient characteristics as age, sex, and diagnosis. We also suggest that researchers wishing to evaluate health and social functioning of persons with serious mental disorders use the total score. Caution is, however, warranted when interpreting the total score for a French-speaking populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 9 publications
9
29
0
2
Order By: Relevance
“…Designed for routine clinical use, the Health of the Nation Outcome Scales (HoNOS) are comprehensive of clinical and social functioning, acceptable to clinicians, sensitive to change, valid and generally reliable (Wing et al, 1998;Amin et al, 1999;Burns et al, 1999a;Orrell et al, 1999;Lauzon et al, 2001;Pirkis et al, 2005b). They cover all ages and are used in Australia, New Zealand and the UK (Wing et al, 1996;Trauer et al, 1999;Pirkis et al, 2005aPirkis et al, , 2005b.…”
Section: Discussionmentioning
confidence: 99%
“…Designed for routine clinical use, the Health of the Nation Outcome Scales (HoNOS) are comprehensive of clinical and social functioning, acceptable to clinicians, sensitive to change, valid and generally reliable (Wing et al, 1998;Amin et al, 1999;Burns et al, 1999a;Orrell et al, 1999;Lauzon et al, 2001;Pirkis et al, 2005b). They cover all ages and are used in Australia, New Zealand and the UK (Wing et al, 1996;Trauer et al, 1999;Pirkis et al, 2005aPirkis et al, , 2005b.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the scale could be subdivided into 4 subscales (‘behavioral problems’, ‘impairment’, ‘symptomatic problems’ and ‘social problems’). However, there is not really much evidence that subscale scores are reliable [14,16,25,26]. Therefore, we only used the HoNOS-D main score and single items for further calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the factor structure identifi ed by Trauer (1999) and Lauzon et al (2001) was also assessed. The goodness-of-fi t of the data was assessed using the fi t indices recommended by Hu andBentler (1999) (standardized-root-mean-square-residual, SRMR, Bentler, 1995) and the root-mean-square-error-ofapproximation (RMSEA, Steiger, 1990) as well as the 'Comparative Fit Index' (CFI, Bentler, 1990).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Lauzon et al (2001) examined a one-dimensional model of the HoNOS-D using confi rmatory factor analysis. In line with the methodological procedure by Lauzon et al (2001) two one-factor-models were examined using Study 1. The fi rst one-dimensional model included items 1 to 10, the second one-dimensional model included items 1 to 12.…”
Section: Factorial Validitymentioning
confidence: 99%
See 1 more Smart Citation